STRATEGI GURU DALAM PEMBELAJARAN SISWA BERKEBUTUHAN KHUSUS DI ERA SOCIETY 5.0: STUDI LITERATUR - Solikah, Binti; Achmad Fathul Iman; Kun Cahyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Society 5.0 era marks a shift toward a human-centered educational ecosystem supported by artificial intelligence, data analytics, and digital connectivity. This study aims to identify and analyze teachers’ strategies in improving the learning of students with special needs in alignment with Society 5.0 principles. This study employs a literature review approach by analyzing scholarly sources published between 2015 and 2025. Data were obtained from journal articles, books, and policy documents retrieved from academic databases. The data were analyzed using a thematic approach to identify effective instructional strategies. The findings reveal four key strategies: (1) data-driven differentiated instruction, (2) the use of accessible assistive technology, (3) structured multidisciplinary collaboration, and (4) strengthening teachers’ pedagogical capacity through communities of practice. The effectiveness of these strategies is influenced by teachers’ digital literacy, infrastructure availability, and institutional policy support. This study recommends strengthening training based on Universal Design for Learning, simplifying instructional administration, and fostering partnerships with educational technology providers. This study contributes to the development of a conceptual framework for inclusive learning in the Society 5.0 era